Endocrine Diseases of Newborn: Epidemiology, Pathogenesis, Therapeutic Options, and Outcome “Current Insights Into Disorders of Calcium and Phosphate in the Newborn” - Taylor-Miller, Tashunka; Allgrove, Jeremy (Frontiers in Pediatrics, 2021)
The physiology and regulation of bone minerals in the fetus and the newborn is significantly different from children and adults. The bone minerals calcium, phosphate, and magnesium are all maintained at higher concentrations in utero to achieve adequate bone accretion. This is an integral component of normal fetal development which facilitates safe neonatal transition to post-natal life. When deciphering the cause of bone mineral disorders in newborns, the potential differential diagnosis list is broad and complex, including several extremely rare conditions. Also, significant discoveries including new embryological molecular genetic transcription factors, the role of active placental mineral transport, and hormone regulation factors have changed the understanding of calcium and phosphate homeostasis in the fetus and the newborn. This article will guide clinicians through an updated review of calcium and phosphate physiology, then review specific conditions pertinent to successful neonatal care. Furthermore, with the advancement of increasingly rapid molecular genetic testing, genomics will continue to play a greater role in this area of fetal diagnostics and prognostication.